Nasopharyngeal Extension of Giant Meningioma - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Meningiomas are common intracranial neoplasms but extracranial meningioma of the paranasal sinus is extremely rare. The recommended treatment of these meningothelial tumors is complete surgical excision. The authors report a 79-year-old woman presenting with facial pain and nasal obstruction for several months. Endoscopic nasopharyngeal examination showed a right nasal mass that arose from the nasopharynx and reached around the middle meatus. Gadolinium-enhanced magnetic resonance imaging showed a well-circumscribed nasopharyngeal mass, which originates from the right rosenmuller fossa and extends to the right nasal cavity. A biopsy was made with nasal endoscopy under local anesthesia for definitive diagnosis. Histopathologic examination was reported as benign meningothelial meningioma. In conclusion, physicians should keep in mind uncommon tumors in the nasal cavity and paranasal sinuses. Surgical resection is the primary treatment choice; however, close follow-up could be an option in patients with comorbidities.
Keywords: Dural tail; endoscopic sinus surgery; extracranial meningioma; paranasal sinus